A brief overview of secondary zinc anode development: The key of improving zinc‐based energy storage systems. (28th July 2017) - Mainar, Aroa R.; Colmenares, Luis C.; Blázquez, J. Alberto; Urdampilleta, Idoia
Summary: Electricity will increasingly be produced from sources that are geographically decentralized and/or intermittent in their nature. In consequents, there is an urgent need to increase the storage of energy to guarantee the continuity of energy supply. Rechargeable zinc‐air battery is a promising technology due to the high theoretical energy density and the abundant and environmentally benign materials that are used. In the state of the art, the information about secondary zinc anode for rechargeable zinc‐air batteries is scarce. The main development of the technology has been lately concentrated on the bifunctional air electrodes while the used zinc anode is mainly based on a planar zinc electrode providing low specific energy densities for the full system. This overview compiles the available information in the literature regarding the development and manufacturing of zinc anodes for electrical rechargeable batteries applications, where secondary porous zinc electrodes are generally desired. In this context, the zinc‐based anode electrode composition (namely, active material, binder, conductive material, current collector, and additives), pretreatments, and processing techniques are described and their impact on the zinc anode performance analyzed. Abstract : This overview compiles the available information in the literature regarding the development and manufacturing of zinc anodes for electrical rechargeable batteries applications. In this context, the zinc‐based anode electrode composition (namely, active material, binder, conductive material, current collector, and additives), pretreatments, and processing techniques are described and their impact on the zinc anode performance analyzed.